2007
DOI: 10.1177/1090198106294652
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Targeted Educational Materials for Smoking Cessation in African Americans Using Transdermal Nicotine

Abstract: This study examines the efficacy of targeted versus standard care smoking cessation materials among urban African American smokers. Five hundred smokers (250 to each group) are randomized to receive a culturally targeted or standard care videotape and print guide. Both groups receive 8 weeks of nicotine patches and reminder telephone calls at Weeks 1 and 3. Process outcomes include material use and salience at 1 and 4 weeks postbaseline. Smoking outcomes include 7-day abstinence, smoking reduction, and readine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…Other studies not covered note possible differences in outcomes due to factors such as comorbidity of psychiatric or substance abuse disorders, low literacy, and low SES, and suggest that culturally tailored interventions may improve lackluster outcomes for interventions with culturally diverse subgroups. 9294 …”
Section: Resultsmentioning
confidence: 99%
“…Other studies not covered note possible differences in outcomes due to factors such as comorbidity of psychiatric or substance abuse disorders, low literacy, and low SES, and suggest that culturally tailored interventions may improve lackluster outcomes for interventions with culturally diverse subgroups. 9294 …”
Section: Resultsmentioning
confidence: 99%
“…For example, interventions delivered via print materials or videos help maintain blinding of those conducting outcome assessments by having nonstudy staff members give participants the intervention materials so that the assessors can remain blind [34]. This will further minimize bias in behavioral RCTs.…”
Section: Practice Implicationsmentioning
confidence: 96%
“…Most importantly, participants are told not to disclose their treatment group to the research assistants, a method recommended by the Evidence-Based Behavioral Medicine Committee [28] and also used effectively in other intervention studies [34]. Our participants are proactively informed at study visits and counseling sessions that they should not tell the research assistant whether or not they are receiving telephone calls.…”
Section: Challenge #5: Blinding Of Outcome Assessorsmentioning
confidence: 99%
“…66 For example, a cessation trial 67 reported no additional benefit to culturally tailored intervention materials compared to non-tailored materials among Blacks using NRT. Given findings in this sample and other samples of PLWH, 57 interventions that specifically target adherence to NRT or pharmacotherapy may be critical to yield better cessation rates.…”
Section: Discussionmentioning
confidence: 99%